The Influence of Flow of Fund, Financial Knowledge, Financial Attitudes and Personality Towards Financial Management Behavior in the Owners MSMEs Kupang City - Foenay, Christien C. (International Journal of Supply Chain Management, 2021)
This study aims to determine The Influence of Flow of Fund, Financial Knowledge, Financial Attitudes, and Personality Towards Financial Management Behavior In The Owners Micro Small and Medium Enterprises (MSMEs) Kupang City. This research is included in associative causal research. The subjects of this study were the owners of the woven fabric MSMEs in Kupang City as many as 30 MSMEs. Data collection techniques using a questionnaire. Validity and reliability tests were carried out on 20 people outside the subject who were registered as woven fabric MSMEs in Kupang City. Analysis prerequisite tests include linearity test, multicollinearity test, and heteroscedasticity test. Data analysis techniques with multiple linear regression. The results showed that (1) there was a positive Influence Of Financial Knowledge On Financial Management Behavior of The Owners Woven Fabric MSMEs Kupang City (2) there was a positive Influence Of Financial Attitudes On Financial Management Behavior of The Owners Woven Fabric MSMEs Kupang City (3) there was a positive Influence Of Personality On Financial Management Behavior of The Owners Woven Fabric MSMEs Kupang City (4) there is a positive Influence of Financial Knowledge, Financial Attitudes, and Personality towards Financial Management Behavior on the The Owners Woven fabric MSMEs Kupang City.